Menghadapi ancaman siber di era society 5.0: Inovasi strategi diplomasi pertahanan untuk stabilitas sosial - Aritonang, Alice Agatha Delfreeta (Universitas Negeri Malang, 2025)
Addressing cyber threats in the society 5.0 era: Strategic innovations in defense diplomacy for social stability The Society 5.0 era introduces the integration of advanced technologies such as Artificial Intelligence (AI), the Internet of Things (IoT), big data, and robotics into the social, political, and economic spheres of global society. Japan, as the pioneer of Society 5.0, formulated this concept as a response to various social challenges, including those related to security and defense diplomacy. This article examines the implications of Society 5.0 for defense diplomacy, particularly in strategies for cyber and non-traditional security, aimed at safeguarding national security and social stability amid technological change. Using a literature review approach and secondary data analysis, this study identifies three key strategies: national security, technological enhancement, and international collaboration. The analysis reveals that defense diplomacy now involves collaborative approaches and digital strategy to respond to modern threats. These findings highlight the importance of international cooperation and increased technological literacy at the community level to support social security in the Society 5.0 era. Era Society 5.0 memperkenalkan integrasi teknologi tinggi seperti kecerdasan buatan (AI), Internet of Things (IoT), big data, dan robotika dalam kehidupan sosial, politik, dan ekonomi masyarakat global. Jepang sebagai pelopor Society 5.0 merumuskan konsep ini sebagai jawaban atas berbagai tantangan sosial, termasuk di bidang keamanan dan diplomasi pertahanan. Artikel ini mengkaji implikasi Society 5.0 dalam diplomasi pertahanan, khususnya pada strategi keamanan siber dan non-tradisional, yang bertujuan untuk melindungi keamanan nasional dan stabilitas sosial di tengah perubahan teknologi. Dengan menggunakan pendekatan literature review dan analisis data sekunder, penelitian ini menemukan tiga strategi utama: keamanan nasional, penguatan teknologi, dan kolaborasi internasional. Hasil analisis menunjukkan bahwa diplomasi pertahanan kini melibatkan pendekatan kolaboratif dan strategi digital untuk merespons ancaman modern. Temuan ini menegaskan pentingnya kolaborasi internasional dan peningkatan literasi teknologi pada tingkat komunitas dalam mendukung keamanan sosial di era Society 5.0.